If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5.4x(x + 9.6) * 4.1 = 3.3 + -6.9x Reorder the terms: -5.4x(9.6 + x) * 4.1 = 3.3 + -6.9x Reorder the terms for easier multiplication: -5.4 * 4.1x(9.6 + x) = 3.3 + -6.9x Multiply -5.4 * 4.1 -22.14x(9.6 + x) = 3.3 + -6.9x (9.6 * -22.14x + x * -22.14x) = 3.3 + -6.9x (-212.544x + -22.14x2) = 3.3 + -6.9x Solving -212.544x + -22.14x2 = 3.3 + -6.9x Solving for variable 'x'. Reorder the terms: -3.3 + -212.544x + 6.9x + -22.14x2 = 3.3 + -6.9x + -3.3 + 6.9x Combine like terms: -212.544x + 6.9x = -205.644x -3.3 + -205.644x + -22.14x2 = 3.3 + -6.9x + -3.3 + 6.9x Reorder the terms: -3.3 + -205.644x + -22.14x2 = 3.3 + -3.3 + -6.9x + 6.9x Combine like terms: 3.3 + -3.3 = 0.0 -3.3 + -205.644x + -22.14x2 = 0.0 + -6.9x + 6.9x -3.3 + -205.644x + -22.14x2 = -6.9x + 6.9x Combine like terms: -6.9x + 6.9x = 0.0 -3.3 + -205.644x + -22.14x2 = 0.0 Begin completing the square. Divide all terms by -22.14 the coefficient of the squared term: Divide each side by '-22.14'. 0.1490514905 + 9.288346883x + x2 = 0 Move the constant term to the right: Add '-0.1490514905' to each side of the equation. 0.1490514905 + 9.288346883x + -0.1490514905 + x2 = 0 + -0.1490514905 Reorder the terms: 0.1490514905 + -0.1490514905 + 9.288346883x + x2 = 0 + -0.1490514905 Combine like terms: 0.1490514905 + -0.1490514905 = 0.0000000000 0.0000000000 + 9.288346883x + x2 = 0 + -0.1490514905 9.288346883x + x2 = 0 + -0.1490514905 Combine like terms: 0 + -0.1490514905 = -0.1490514905 9.288346883x + x2 = -0.1490514905 The x term is 9.288346883x. Take half its coefficient (4.644173442). Square it (21.56834696) and add it to both sides. Add '21.56834696' to each side of the equation. 9.288346883x + 21.56834696 + x2 = -0.1490514905 + 21.56834696 Reorder the terms: 21.56834696 + 9.288346883x + x2 = -0.1490514905 + 21.56834696 Combine like terms: -0.1490514905 + 21.56834696 = 21.4192954695 21.56834696 + 9.288346883x + x2 = 21.4192954695 Factor a perfect square on the left side: (x + 4.644173442)(x + 4.644173442) = 21.4192954695 Calculate the square root of the right side: 4.628098472 Break this problem into two subproblems by setting (x + 4.644173442) equal to 4.628098472 and -4.628098472.Subproblem 1
x + 4.644173442 = 4.628098472 Simplifying x + 4.644173442 = 4.628098472 Reorder the terms: 4.644173442 + x = 4.628098472 Solving 4.644173442 + x = 4.628098472 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.644173442' to each side of the equation. 4.644173442 + -4.644173442 + x = 4.628098472 + -4.644173442 Combine like terms: 4.644173442 + -4.644173442 = 0.000000000 0.000000000 + x = 4.628098472 + -4.644173442 x = 4.628098472 + -4.644173442 Combine like terms: 4.628098472 + -4.644173442 = -0.01607497 x = -0.01607497 Simplifying x = -0.01607497Subproblem 2
x + 4.644173442 = -4.628098472 Simplifying x + 4.644173442 = -4.628098472 Reorder the terms: 4.644173442 + x = -4.628098472 Solving 4.644173442 + x = -4.628098472 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.644173442' to each side of the equation. 4.644173442 + -4.644173442 + x = -4.628098472 + -4.644173442 Combine like terms: 4.644173442 + -4.644173442 = 0.000000000 0.000000000 + x = -4.628098472 + -4.644173442 x = -4.628098472 + -4.644173442 Combine like terms: -4.628098472 + -4.644173442 = -9.272271914 x = -9.272271914 Simplifying x = -9.272271914Solution
The solution to the problem is based on the solutions from the subproblems. x = {-0.01607497, -9.272271914}
| -4x+3(2.5x-19)=-15 | | (10x-75)-(3.2y+7.9)= | | 14-12-5k=6 | | 2(n+3)=34-2n | | 1.5/50 | | 10x-3=317 | | 45n+35n= | | P(x)=8-4x | | 16=12y+5x | | -7.9t+19.18=-18.19-11.6t | | (X+8)+(9x-7)= | | x/6=2x-78.5 | | 4x+3=5x-9 | | (X-3)(x+2)=-2(x-3) | | x=-6x+21 | | 0.09xX=85.92 | | 20a^3+65a^2-60a=0 | | 6x^2+2x-104=0 | | 15y=-18x+30 | | -40+3p=2 | | 4(v+8)=9v+27 | | 6=w/19.2 | | 12c^2-17c+6=0 | | 2*3.14*r=110 | | 22.4=7v | | 4(2x-5)=x+2 | | -32-4x=6(x-6)-8x | | X-2=8x | | x-4-1=-1-5x+8x | | 8x-(4x-8)=8 | | 9+2(7u-5)=-2(5u-4)+6u | | 2x+28=90 |